EVALUASI PROSES PEMBELAJARAN IPA BIOLOGI BERBASIS SCIENTIFIC APPROACH PADA MATERI PENCEMARAN LINGKUNGAN KELAS VII DI SMP MUHAMMADIYAH SE-KECAMATAN MERGANGSAN YOGYAKARTA - Anggraini, Agustina Novita; Aprilia, Nani (Lentera: Jurnal Ilmiah Kependidikan, 2020)
Implementation of the 2013 curriculum requires teachers to carry out scientific approach-based learning, but not all teachers have participated in the 2013 curriculum application training so that the learning process by applying the 2013 curriculum still experiences many obstacles. This study aims to evaluate the learning process of Biological Science on Environmental Pollution material in class VII Muhammadiyah Junior High Schools in Mergangsan sub-district with a scientific approach. This type of research is evaluation research. The study population was SMP Muhammadiyah in Mergangsan sub-district, which amounted to 2 schools. The school sampling technique used a saturated sampling technique so that the two Muhammadiyah schools in Mergangsan sub-district were all used, namely SMP Muhammadiyah 9 Yogyakarta and MTS Muhammadiyah. The science teacher used the research sample with the sampling technique using purposive sampling, and the sample class with the sampling technique was simple random sampling so that SMP Muhammadiyah 9 Yogyakarta obtained class VII A while MTS Muhammadiyah Karangkajen class VII C. using data collection instruments, observation sheets and documentation guidelines. The data obtained were analyzed descriptively quantitatively. The results of the study are as follows: 1) The learning process with a scientific approach at SMP Muhammadiyah in Mergangsan sub-district is in accordance with Permendikbud No.103 2014 and Permendikbud No. 22 of 2016. 2) The learning process with the application of the scientific approach at SMP Muhammadiyah in Mergangsan sub-district, the aspects of preliminary activities get a percentage of 76.69% in the "good" category, core activities are 75.57% in the "good" category and 66.67% closing activities category "good"